Association between interpregnancy interval and adverse birth outcomes in women with a previous stillbirth: an international cohort study - Regan, Annette; Gissler, M.; Magnus, M.C.; Håberg, S.E.; Ball, Stephen; Malacova, Eva; Nassar, N.; Leonard, H.; Pereira, Gavin (ELSEVIER SCIENCE INC, 2019)
Background: WHO recommends that women wait at least 2 years after a livebirth and at least 6 months after a miscarriage or induced abortion before conceiving again, to reduce the risk of adverse birth outcomes in the subsequent pregnancy. No recommendation exists for the optimal interval after a stillbirth. We investigated the association between interpregnancy interval after stillbirth and birth outcomes in the subsequent pregnancy. Methods: In this international cohort study, we used data from birth records from Finland (1987–2016), Norway (1980–2015), and Western Australia (1980–2015). Consecutive singleton pregnancies in women whose most recent pregnancy had ended in stillbirth of at least 22 weeks' gestation were included in the analysis. Interpregnancy interval was defined as the time between the end of pregnancy (delivery date) and the start of the next pregnancy (delivery date of next pregnancy minus gestational age at birth). We calculated odds ratios (ORs) for stillbirth, preterm birth, and small-for-gestational-age birth by interpregnancy interval by country, adjusted for maternal age, parity, decade of delivery, and gestational length of the previous pregnancy. A fixed-effects meta-analysis was used to estimate pooled ORs. Findings: We identified 14 452 births in women who had a stillbirth in the previous pregnancy; median interpregnancy interval after stillbirth was 9 months (IQR 4–19). 9109 (63%) women conceived within 12 months of the stillbirth. Of the 14 452 births, 228 (2%) were stillbirths, 2532 (18%) were preterm births, and 1284 (9%) were small-for-gestational-age births. Compared with an interpregnancy interval of 24–59 months, intervals shorter than 12 months were not associated with increased odds of subsequent stillbirth (pooled adjusted OR 1·09 [95% CI 0·63–1·91] for <6 months; 0·90 [0·47–1·71] for 6–11 months), preterm birth (0·91 [0·75–1·11] for <6 months; 0·91 [0·74–1·11] for 6–11 months), or small-for-gestational-age birth (0·66 [0·51–0·85] for <6 months; 0·64 [0·48–0·84] for 6–11 months). Further, we noted no difference in the association between interpregnancy interval and birth outcomes by gestational length of the previous stillbirth. Interpretation: Conception within 12 months of a stillbirth was common and was not associated with increased risk of adverse outcomes in the subsequent pregnancy. These findings could be used when counselling women who are planning future pregnancies after a stillbirth and for informing future recommendations for pregnancy spacing in a high-income setting. Funding: National Health and Medical Research Council (Australia), and Research Council of Norway.